Life expectancy after the first suicide attempt. (14th December 2017) - Jokinen, J.; Talbäck, M.; Feychting, M.; Ahlbom, A.; Ljung, R.
Abstract : Objective: To assess excess mortality among suicide attempters compared to the general population. Method: Remaining life expectancy was calculated for a nationwide cohort of all 187 894 persons 18 years or older hospitalised for the first time attempted suicide in Sweden in 1971–2010. Results: Life expectancy was shortened throughout the lifespan for both men and women debuting with suicide attempt. The reduction in life expectancy for men debuting with a suicide attempt at 20 years of age was 18 years while the reduction for men debuting at 50 years of age was 10 years. For women attempting suicide, the life expectancy was shortened by 11 and 8 years respectively. The gender difference in life expectancy attenuated in patients making their first suicide attempt at age 70 years or older. Suicide deaths explained about 20% of the total mortality within 10 years of the suicide attempt and 5% in those with duration of four decades since the first suicide attempt. Conclusion: The life expectancy is dramatically reduced in patients attempting suicide. With most excess deaths being due to physical health conditions, public efforts should be directed both towards improving physical health and to prevent suicide.